Real Convergence to EU Income Levels : Central Europe From 1990 to the Long Term - Jiang, Guorong (IMF Working Papers; Working Paper, 2001)
The paper discusses factors likely to shape the nature and pace of economic growth of five Central European transition countries now engaged in accession to the European Union. It is organized around the standard growth accounting framework. The paper reviews the growth of these countries since 1990 and draws lessons from the growth experiences of other regions since the 1950s, shedding light on long-term growth prospects for these countries. It discusses a set of growth calculations and highlights the key uncertainties in them.